Integrating Phonological Component Analysis with Language Therapy for Pediatric Acquired Aphasia - Banu, Thasneem; Divya, Dronadula; Gupta, Rajshree (Journal of Educational Research and Policies, 2025)
This case study presents a 7-year-old girl diagnosed with Acquired Childhood Aphasia (ACA) post-stroke, resulting in severe language and cognitive impairments. Treatment with Phonological Component Analysis (PCA) and language therapy led to significant improvements, suggesting PCA as a promising intervention for ACA, where established treatments for ACA are still lacking.